Utilização da corrente crítica no gerenciamento de uma obra no setor da construção civil - Cavalcanti, Nathalie da Silva (2011)
There is a growing need to improve management in civil construction. Therefore this work focuses on demonstrating the applicability of a new project management methodology, based on the Theory of Constraints, called Critical Chain Project Management (CCPM), which can collaborates with civil construction management. The research method was an action research in a medium company with two implementation phases. In the first phase, the construction of two semi-detached houses planning was formulated and the results were analyzed. The second phase was to understand and improve the implementation process in an attempt to eliminate or reduce the problems identified at the first phase. The second phase results showed that the CCPM approach increased the team's focus, presented a simple and visual control of the work status, motivated people and teamwork; increased productivity and reduced the multitasking. However, the process required time and dedication for the planning, changed habits, culture and thoughts, besides that it required consensus among stakeholders.